Surgical Approach to Dentigerous Cyst with Protection of the Inferior Alveolar Nerve - Dalampiras Stylianos; Vakirtzian Georgios-Alexandros; Dalampiras Foivos-Antonios; Dalampira Maria (Balkan Stomatological Society, 2016)
Aim: To stress the importance of surgical planning when treating large dentigerous cysts.